Pengembangan Modul Praktikum Tematik pada Prodi Pendidikan Islam Anak Usia Dini - Agusriani, Ade; Latuconsina, Nur Khalisah; Ismail, Wahyuni; M. Rusdi; Kusyairy, Umi; Rahman, Ulfiani (NANAEKE: Indonesian Journal of Early Childhood Education, 2024)
Teaching materials are an important element in the learning process that facilitates students to understand concepts while providing practical experience in their application, however, currently, the availability of teaching modules is still very limited, including for thematic learning. This research aims to develop a thematic practicum module in the Early Childhood Islamic Education Study Program. This research is a research and development (R&D) 4D model (Define, Design, Develop, Disseminate) with a one-shot case study design, which aims to develop a pre-existing product as a thematic learning module. Data analysis uses quantitative techniques. The research results include thematic-based practicum modules which were developed taking into account the developmental needs of early childhood and thematic learning principles that encourage learning through real experience and play which then go through a validation stage by experts. Thus, it can be concluded that the development of thematic practicum modules in the Early Childhood Islamic Education Study Program (PIAUD) has met the validity category to support thematic learning.